Asia and its various growing dimensions of globalisation for economic integration - Mitrajit Biswas (Journal of BRICS Studies)
The paper would try to look at the India-China relations of cooperation within BRICS framework. A comparison of this stance with India and China in power struggle Asia would form another part of the paper. India has opened up new platforms on either side of the subcontinent such as Bay of Bengal Initiative for Multi Sectoral Technical Cooperation, Chabahar port project as well as joined Shanghai Cooperation Organization as its means of outreach. This has all been a part of India’s changing role in Asia. However, it must be also kept in mind that there is a China-Pakistan angle to it. A battle for power and influence has been there in the region of South Asia even before the pandemic. Now post covid19 scenario as the western world shrinks and the power fulcrum shifting towards Asia with USA pivot to Asia program as well as the geo-political tensions between USA and China coming up there is a new role for South Asia right now. The paper would like to understand these scenarios with an eye on India-China relations in a cooperative competition relationship scenario. On one side of the paper the joint role of India-China in BRICS framework would be looked at against the Indo-Pacific Asian power struggle.